Short communication: Predicting cation exchange capacity from hygroscopic moisture in agricultural soils of Western Europe - Torrent, José; del Campillo, María C.; Barrón, Vidal (Spanish Journal of Agricultural Research, 2015)
Soil cation exchange capacity (CEC) depends on the extent and negative charge density of surfaces of soil mineral and organic components. Soil water sorption also depends on the extent of such surfaces, giving thus way to significant relationships between CEC and hygroscopic moisture (HM) in many soils. In this work, we explored whether CEC could be accurately predicted from HM in agricultural soils of Mediterranean and humid temperate areas in Western Europe. For this purpose, we examined 243 soils across a wide variation range of their intrinsic properties. Soil CEC was determined using 1 M ammonium acetate at pH 7 and HM at an equilibrium air relative humidity (RH) of 43% (HM43). Most of the variation of soil CEC was explained by HM43 through a linear function (CEC = 1.4 + 0.78HM43; R2 = 0.962; standard deviation = 2.30 cmolc/kg). Coefficients of the regression equation were similar for subgroups of soils differing in moisture regime, clay mineralogy, carbonate content and organic carbon content. Therefore, soil hygroscopic moisture measurements at a fixed RH level provided a simple, robust, inexpensive method for predicting soil CEC.